Stabilizing rammed earth using xanthan gum or animal glue as bio-binder - Abdelaal, Ahmed; Ma, Jiaming; Gomaa, Mohamed; Giustozzi, Filippo; Xie, Yi Min (Frontiers in Built Environment, 2025)
Rammed earth (RE) construction has gained increasing interest in recent years owing to sustainability demands in the construction industry and the advancement of digital fabrication techniques. However, the domination of the cement-stabilized RE material in the RE industry poses environmental concerns due to the substantial carbon emissions associated with cement production. In this study, bio-based alternatives to cement-stabilized RE are investigated through evaluating xanthan gum (XG) and animal glue (AG) as bio-binders for RE stabilization. Unconfined compressive strength tests are conducted on XG and AG-stabilized specimens for mechanical performance evaluation, and unstabilized RE samples as baseline for comparison. Results show that AG-stabilized specimens demonstrate a 294% strength improvement over unstabilized RE, reaching 6.86 MPa at 28 days, while XG-stabilized specimens achieve a 221% improvement. XG-stabilized specimens, however, exhibit susceptibility to microbial proliferation. The findings from this research demonstrate that XG and AG have the potential to be viable alternatives to mainstream RE construction methods, paving the way for advancing environmentally friendly RE construction.